Quantifying the release of climate-active gases by large meteorite impacts with a case study of Chicxulub - Morgan,JV; Artemieva,N; Expedition,364 Science Party (Geophysical Research Letters, 2017)
Potentially hazardous asteroids and comets have hit Earth throughout its history, with catastrophic consequences in the case of the Chicxulub impact. Here we reexamine one of the mechanisms that allow an impact to have a global effect—the release of climate-active gases from sedimentary rocks. We use the SOVA hydrocode and model ejected materials for a sufficient time after impact to quantify the volume of gases that reach high enough altitudes (> 25 km) to have global consequences. We vary impact angle, sediment thickness and porosity, water depth, and shock pressure for devolatilization and present the results in a dimensionless form so that the released gases can be estimated for any impact into a sedimentary target. Using new constraints on the Chicxulub impact angle and target composition, we estimate that 325 ± 130 Gt of sulfur and 425 ± 160 Gt CO2 were ejected and produced severe changes to the global climate.